2012
DOI: 10.2147/ijicmr.s29352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of air pollution on lung inflammation and the role of Toll-like receptors

Abstract: Abstract:The link between air pollution and adverse pulmonary health effects is well established. The National Ambient Air Quality Standards were formulated to protect human health. These standards are strictly enforced based on strong associations between elevated air pollution levels and increased emergency room visits and hospitalizations due to respiratory conditions. Impacts of air pollution on lung health occur due to the direct interaction between the external environment and internal biological systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 123 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Results from in vitro experiments cannot fully explain exposure-related health outcomes in workers, as individual susceptibility naturally varies due to genetic polymorphisms, underlying health conditions, age, nicotine use, BMI, or external factors, such as long-term exposure to weak electro-magnetic fields (Hosseinabadi et al 2019 ; Plummer et al 2012 ; Schwartz and Cook 2005 ). However, based on the in vitro results in the present study, it can be assumed that occupational exposure during waste handling may elicit an immune response in susceptible workers.…”
Section: Discussionmentioning
confidence: 99%
“…Results from in vitro experiments cannot fully explain exposure-related health outcomes in workers, as individual susceptibility naturally varies due to genetic polymorphisms, underlying health conditions, age, nicotine use, BMI, or external factors, such as long-term exposure to weak electro-magnetic fields (Hosseinabadi et al 2019 ; Plummer et al 2012 ; Schwartz and Cook 2005 ). However, based on the in vitro results in the present study, it can be assumed that occupational exposure during waste handling may elicit an immune response in susceptible workers.…”
Section: Discussionmentioning
confidence: 99%
“…To protect human health, the US EPA has established the NAQS to regulate "criteria" of air pollutants: O 3 , PM, NO x , SO x , lead, and carbon monoxide (CO). Regulation of these criteria through the Clean Air Act is based on the scientific evidence that exposure to air pollution is associated with the development (long-term effect) or exacerbation (short-term effect) of a variety of respiratory conditions (Plummer, Smiley-Jewell, and Pinkerton, 2012). Acute and chronic exposures to atmospheric gases and PM are associated with increased emergency room visits and hospital admissions for exacerbations of pulmonary conditions, including asthma and chronic obstructive pulmonary disease.…”
Section: Lung Inflammationmentioning
confidence: 99%
“…These effects may result from direct interaction of air pollutants with various receptors or via interactions with secondary mediators within these inflammatory pathways. Numerous investigations of air pollution-induced health effects are investigating the mechanism behind the inflammatory response to inhaled air pollutants using human, laboratory, and cellular systems (Plummer, Smiley-Jewell, and Pinkerton, 2012). It has just been reported (see Section 10.2) that PM physicochemical nature is influenced by many factors such as particle size, emission season, and site; in such a way it seems difficult to understand which is the contribution promoting the inflammatory pathways.…”
Section: Lung Inflammationmentioning
confidence: 99%
“…A large number of epidemiological and pathological studies have shown that pollutants in the air can cause serious lung diseases [5], including particulate matter (PM 2.5 , PM 10 ), sulfur dioxide (SO 2 ), carbon monoxide (CO) and nitrogen oxide (NOx) being capable of causing asthma and tuberculosis. At the same time, other systems and organs of the body can also be harmed to varying degrees if people are exposed to air pollution for a long time [6][7][8][9], and when the amount and concentration of air pollutant increases obviously, even that can indirectly affect the health of human beings through permeation into food products that people usually eat [10,11]. This introduces an urgent need for people to have a certain degree of understanding of air quality in order to adopt operations to manage air quality.…”
Section: Introductionmentioning
confidence: 99%